Relativistic polarization analysis of Rayleigh scattering by atomic hydrogen - Safari, Laleh; Amaro, Pedro; Tashenov, Stanislav (Physical review. A, Atomic, molecular, and optical physics, 2012)
A relativistic analysis of the polarization properties of light elastically scattered by atomic hydrogen is performed, based on the Dirac equation and second-order perturbation theory. The relativistic atomic states used for the calculations are obtained by making use of the finite basis set method and are expressed in terms of B splines and B polynomials. We introduce two experimental scenarios in which the light is circularly and linearly polarized, respectively. For each of these scenarios, the polarization-dependent angular distribution and the degrees of circular and linear polarization of the scattered light are investigated as a function of scattering angle and photon energy. Analytical expressions are derived for the polarization-dependent angular distribution which can be used for scattering by both hydrogenic as well as many-electron systems. Detailed computations are performed for Rayleigh scattering by atomic hydrogen within the incident photon energy range 0.5 to 5 keV. Particular attention is paid to the effects that arise from higher (nondipole) terms in the expansion of the electron-photon interaction.
Gesehen am 11.06.2018